Pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, and optical member

Through the combination of (meth)acrylic polymers and copolymers of specific structures and organosiloxane compounds, the problems of easy peelability of the adhesive layer in the initial stage and high adhesive strength after heating in the display equipment manufacturing are solved, and the stability and strength requirements of the adhesive layer are achieved.

JP7627575B2Active Publication Date: 2025-02-06NIPPON CARBIDE KOGYO KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021021946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-15
Publication Date
2025-02-06
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to form a pressure-sensitive adhesive layer in the early stage with easy peelability but high adhesive strength after heating during the manufacturing process of the display device, and the adhesive layer is not easily damaged over time.

Method used

Using an adhesive composition containing (meth)acrylic polymers and copolymers of specific structural units, combining silicone compounds with organosiloxane skeletons and specific side chain groups, the initial easy peelability of the adhesive layer and high adhesion strength after heating are achieved by adjusting the molecular weight and content.

Benefits of technology

An adhesive layer that is easy to peel and not easily damaged in the initial stage and maintains high bond strength after heating is achieved, suitable for bonding and transportation of various components during display equipment manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627575000001
    Figure 0007627575000001
  • Figure 0007627575000002
    Figure 0007627575000002
  • Figure 0007627575000003
    Figure 0007627575000003
Patent Text Reader

Abstract

To provide an adhesive composition and the like capable of forming an adhesive layer which exhibits light peelability at the initial stage of bonding, hardly impairs the light peelability with time, and exhibits high adhesive force after heating.SOLUTION: The adhesive composition contains: a (meth)acrylic polymer (A) which contains a monomer unit having a crosslinkable functional group and has a Tg lower than 0°C; a (meth)acrylic copolymer (B) which contains 0.1-10 mass% of a monomer unit having an organosiloxane skeleton based on all the constituent units and has an Mw of 10,000-400,000; a silicone compound (C) which has an epoxy group and / or a polyether group in a side chain and has a kinematic viscosity (25°C) of 2,000 mm2 / s or less; and a crosslinking agent. The Mn of the monomer having the organosiloxane skeleton in the copolymer (B) is 4,000 or more and less than 20,000, the content of the copolymer (B) is 0.1-21 pts.mass based on 100 pts.mass of the polymer (A), and the content of the silicone compound (C) is 0.1-10 pts.mass based on 100 pts.mass of the polymer (A).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet, and an optical member. [Background technology]

[0002] Pressure-sensitive adhesive compositions used in various display devices are required to be able to form a pressure-sensitive adhesive layer that exhibits easy peelability at the initial stage of lamination and high adhesive strength after heating. In response to such requirements, various pressure-sensitive adhesive compositions have been developed.

[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition comprising 100 parts by mass of a polymer (A) having a glass transition temperature of less than 0° C., and 0.1 to 20 parts by mass of a copolymer (B) having a weight average molecular weight in the range of 10,000 or more and less than 100,000, the copolymer including, as monomer units, a monomer having an organosiloxane skeleton and a functional group equivalent in the range of 1,000 g / mol or more and less than 15,000 g / mol, and a monomer having a homopolymer glass transition temperature of 40° C. or more. Furthermore, for example, Patent Document 2 discloses a pressure-sensitive adhesive composition comprising 100 parts by mass of a polymer (A) having a glass transition temperature of less than 0°C, and 0.1 to 20 parts by mass of a copolymer (B) having a weight average molecular weight of 10,000 or more and less than 100,000, the copolymer (B) comprising, as monomer units, a monomer (B1) having an organosiloxane skeleton and a functional group equivalent in the range of 1,000 g / mol or more and 4,600 g / mol or less, and a monomer (B2) having a homopolymer glass transition temperature of 40°C or more, wherein the copolymer (B) is a copolymer containing 10% by mass to 20% by mass of monomer (B1) and 30% by mass to 50% by mass of monomer (B2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 163115 [Patent Document 2] JP 2017-203164 A Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, in the manufacture of various display devices, various members are attached to an adherend via a pressure-sensitive adhesive layer, and then transported, stored, etc., and it may take time to move to the next step. Therefore, pressure-sensitive adhesive compositions used in various display devices are also required to be capable of forming a pressure-sensitive adhesive layer whose easy peelability at the initial stage of attachment is unlikely to deteriorate over time.

[0006] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of bonding, is unlikely to lose this easy releasability over time, and exhibits high adhesive strength after heating. The problem that another embodiment of the present disclosure aims to solve is to provide an adhesive sheet having an adhesive layer that exhibits easy releasability at the initial stage of application, that is unlikely to lose this easy releasability over time, and that exhibits high adhesive strength after heating. Another problem that another embodiment of the present disclosure aims to solve is to provide an optical component having an adhesive layer that exhibits easy releasability at the initial stage of bonding, that is unlikely to lose this easy releasability over time, and that exhibits high adhesive strength after heating. [Means for solving the problem]

[0007] Specific means for solving the problems include the following aspects. <1> A (meth)acrylic polymer (A) containing a structural unit derived from a monomer having a crosslinkable functional group and having a glass transition temperature of less than 0°C; a (meth)acrylic copolymer (B) containing 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, based on all structural units, and having a weight average molecular weight of 10,000 to 400,000; It has at least one of an epoxy group and a polyether group in the side chain, and has a kinetic viscosity of 2000 mm at 25°C. 2 / s or less of a silicone compound (C); A cross-linking agent; Including, the number average molecular weight of the monomer having an organosiloxane skeleton in the (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000; the content of the (meth)acrylic copolymer (B) is 0.1 parts by mass to 21 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer (A); The pressure-sensitive adhesive composition, wherein the content of the silicone compound (C) is 0.1 to 10 parts by mass based on 100 parts by mass of the (meth)acrylic polymer (A).

[0008] <2> The monomer having an organosiloxane skeleton is a compound represented by the following formula (I): <1> The pressure-sensitive adhesive composition according to claim 1.

[0009] [ka]

[0010] In formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group. m and n each independently represent 0 or an integer of 1 or more, provided that m and n are not 0 at the same time.

[0011] <3> <1> or <2> A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1. <4> <1> or <2> An optical member comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1. Effect of the Invention

[0012] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of bonding, that is unlikely to lose this easy releasability over time, and that exhibits high adhesive strength after heating. According to another embodiment of the present disclosure, there is provided an adhesive sheet including an adhesive layer that exhibits easy releasability at the initial stage of attachment, that is unlikely to lose this easy releasability over time, and that exhibits high adhesive strength after heating. Furthermore, according to another embodiment of the present disclosure, there is provided an optical member including a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of bonding, that is unlikely to lose this easy releasability over time, and that exhibits high adhesive strength after heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, and optical member of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.

[0014] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values ​​before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0015] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when the adhesive composition contains multiple substances corresponding to each component, the amount of each component in the adhesive composition means the total amount of the multiple substances present in the adhesive composition, unless otherwise specified.

[0016] In the present disclosure, the term "(meth)acrylic (co)polymer" refers to a (co)polymer in which the content of structural units derived from a monomer having a (meth)acryloyl group is 50% by mass or more of all structural units (i.e., all structural units of the (meth)acrylic (co)polymer). Here, the term "(co)polymer" refers to a polymer or a copolymer.

[0017] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".

[0018] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.

[0019] In the present disclosure, "after heating" means, for example, after heating to 50° C. or higher. The upper limit of the temperature is, for example, 300° C.

[0020] In the present disclosure, the specific (meth)acrylic polymer (A) and the specific (meth)acrylic copolymer (B) are collectively referred to as the "specific (meth)acrylic polymer."

[0021] [Adhesive composition] The pressure-sensitive adhesive composition of the present disclosure comprises a (meth)acrylic polymer (A) (hereinafter also referred to as "specific (meth)acrylic polymer (A)") that contains structural units derived from a monomer having a crosslinkable functional group and has a glass transition temperature of less than 0°C; a (meth)acrylic copolymer (B) (hereinafter also referred to as "specific (meth)acrylic copolymer (B)") that contains 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, based on the total structural units, and has a weight-average molecular weight of 10,000 to 400,000; and a (meth)acrylic copolymer (B) (hereinafter also referred to as "specific (meth)acrylic copolymer (B)") that has at least one of an epoxy group and a polyether group in a side chain and has a kinetic viscosity at 25°C of 2,000 mm. 2The (meth)acrylic copolymer (B) has a number average molecular weight of 4,000 or more and less than 20,000, the content of the (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer (A), and the content of the silicone compound (C) is 0.1 to 10 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer (A). The pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of application, is unlikely to lose this easy releasability over time, and exhibits high adhesive strength after heating. The reason why the pressure-sensitive adhesive composition of the present disclosure can exhibit such an effect is unclear, but the present inventors speculate as follows, however, the following speculation is not intended to limit the pressure-sensitive adhesive composition of the present disclosure, but is merely an example.

[0022] The monomer having an organosiloxane skeleton has a low polarity derived from its structure, and therefore tends to cause the specific (meth)acrylic copolymer (B) to be unevenly distributed on the adhesive surface of the pressure-sensitive adhesive layer. Here, the "adhesive surface of the pressure-sensitive adhesive layer" may be, for example, the interface between the pressure-sensitive adhesive layer and the adherend. In the pressure-sensitive adhesive composition of the present disclosure, by adjusting the content of constituent units derived from a monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B), the number average molecular weight of the monomer having an organosiloxane skeleton, and the content ratio of the specific (meth)acrylic copolymer (B) to the specific (meth)acrylic polymer (A), it is possible to appropriately unevenly distribute the specific (meth)acrylic copolymer (B) on the adhesive surface of the pressure-sensitive adhesive layer. It is presumed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure exhibits easy peelability from the adherend in the early stages of attachment because the specific (meth)acrylic copolymer (B) is appropriately unevenly distributed on the adhesive surface.

[0023] The pressure-sensitive adhesive composition of the present disclosure contains the specific (meth)acrylic polymer (A), and the pressure-sensitive adhesive layer formed therefrom exhibits wettability to an adherend. The specific silicone compound (C) tends to be unevenly distributed on the adhesive surface of the pressure-sensitive adhesive layer due to its low polarity derived from its structure. In the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, the specific silicone compound (C) is appropriately unevenly distributed on the adhesive surface, and is considered to suppress excessive wet spreading of the pressure-sensitive adhesive layer to the adherend. Therefore, it is presumed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure is unlikely to lose its light peelability at the initial stage of lamination over time.

[0024] The adhesive surface of the pressure-sensitive adhesive layer where the specific (meth)acrylic copolymer (B) is unevenly distributed tends to harden, and the pressure-sensitive adhesive layer tends to be less likely to exhibit high adhesive strength even when heated. In addition to the specific (meth)acrylic copolymer (B), the specific silicone compound (C) is appropriately unevenly distributed on the adhesive surface of the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure. The adhesive surface of the pressure-sensitive adhesive layer where the specific silicone compound (C) is unevenly distributed is considered to be less likely to harden, unlike the adhesive surface of the pressure-sensitive adhesive layer where the specific (meth)acrylic copolymer (B) is unevenly distributed. For this reason, it is presumed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure exhibits high adhesive strength after heating.

[0025] In contrast to the adhesive composition of the present disclosure, the adhesive compositions described in Patent Document 1 (International Publication No. 2015 / 163115; hereinafter the same) and Patent Document 2 (JP Patent Publication No. 2017-203164; hereinafter the same) do not contain the specific silicone compound (C) of the present disclosure, and therefore are considered not to suppress the wetting and spreading of the adhesive layer onto the adherend. For this reason, it is presumed that the adhesive layers formed by the adhesive compositions described in Patent Documents 1 and 2 are prone to losing their easy peelability at the initial stage of lamination over time.

[0026] The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure can exhibit sufficiently high adhesive strength even when heated at a lower temperature (50°C) than conventional temperatures (approximately 70°C).

[0027] [Specific (meth)acrylic polymer (A)] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic polymer (A) [i.e., specific (meth)acrylic polymer (A)] which contains a constituent unit derived from a monomer having a crosslinkable functional group and has a glass transition temperature of less than 0°C.

[0028] <Structural Unit Derived from Monomer Having Crosslinkable Functional Group> The specific (meth)acrylic polymer (A) contains a constituent unit derived from a monomer having a crosslinkable functional group. The crosslinkable functional group of the constitutional unit derived from a monomer having a crosslinkable functional group can contribute to crosslinking with a crosslinking agent described below.

[0029] In the present disclosure, the term "structural unit derived from a monomer having a crosslinkable functional group" refers to a structural unit formed by addition polymerization of a monomer having a crosslinkable functional group.

[0030] An example of a monomer having a crosslinkable functional group is a monomer having at least one crosslinkable functional group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.

[0031] The type of crosslinkable functional group is not particularly limited. Specific examples of the crosslinkable functional group include a hydroxyl group, a carboxyl group, and an amino group. The term "amino group" as used herein refers to a primary amino group and / or a secondary amino group. The crosslinkable functional group is preferably at least one of a hydroxyl group and a carboxy group.

[0032] The type of the monomer having a hydroxyl group is not particularly limited. Specific examples of monomers having a hydroxyl group include 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl (meth)acrylate. butyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. As the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl(meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and 2-hydroxyethyl acrylate (2HEA) is particularly preferred.

[0033] The type of the monomer having a carboxy group is not particularly limited. Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,MaExamples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate. As the monomer having a carboxy group, for example, acrylic acid (AA) is preferred from the viewpoint of good reactivity with a crosslinking agent (particularly, an isocyanate-based crosslinking agent).

[0034] The type of the monomer having an amino group is not particularly limited. Specific examples of monomers having a primary amino group include acrylamide and methacrylamide. Specific examples of the monomer having a secondary amino group include N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, and N-methoxyethyl(meth)acrylamide.

[0035] The specific (meth)acrylic polymer (A) may contain only one type of structural unit derived from a monomer having a crosslinkable functional group, or may contain two or more types.

[0036] The content of the structural units derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) is not particularly limited, but for example, relative to all structural units of the specific (meth)acrylic polymer (A), is preferably 1 mass% to 40 mass%, more preferably 1 mass% to 35 mass%, even more preferably 2 mass% to 30 mass%, even more preferably 2 mass% to 25 mass%, and particularly preferably 3 mass% to 20 mass%. When the content of the structural units derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) is within the above range relative to all structural units of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer can be formed in which the easy peelability at the initial stage of bonding is less likely to be impaired over time.

[0037] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic polymer (A) preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.

[0038] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer.

[0039] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. Note that the "(meth)acrylic acid alkyl ester monomer" in the specific (meth)acrylic polymer (A) does not include a monomer that corresponds to a monomer having a crosslinkable functional group. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.

[0040] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. As the (meth)acrylic acid alkyl ester monomer, for example, from the viewpoint of easiness in producing a (meth)acrylic copolymer having a glass transition temperature of less than 0°C, at least one selected from the group consisting of n-butyl acrylate (n-BA), methyl acrylate (MA), and 2-ethylhexyl acrylate (2EHA) is preferred.

[0041] When the specific (meth)acrylic polymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, it may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or it may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.

[0042] When the specific (meth)acrylic polymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic polymer (A) is not particularly limited, but for example, relative to all structural units of the specific (meth)acrylic polymer (A), is preferably 50 mass% or more, more preferably 50 mass% to 99 mass%, even more preferably 60 mass% to 99 mass%, even more preferably 65 mass% to 99 mass%, even more preferably 70 mass% to 98 mass%, even more preferably 75 mass% to 98 mass%, and particularly preferably 80 mass% to 97 mass%. Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic polymer (A) means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic polymer (A).

[0043] <Other building blocks> The specific (meth)acrylic polymer (A) may contain structural units (so-called other structural units) other than the above-described structural units, i.e., the structural unit derived from a monomer having a crosslinkable functional group, which is an essential structural unit, and the structural unit derived from a (meth)acrylic acid alkyl ester monomer, which is an optional structural unit, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0044] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.

[0045] When the specific (meth)acrylic polymer (A) contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.

[0046] When the specific (meth)acrylic polymer (A) contains other structural units, the content of the other structural units in the specific (meth)acrylic polymer (A) is not particularly limited and can be appropriately set depending on the purpose as long as the effects of the pressure-sensitive adhesive composition of the present disclosure are not impaired.

[0047] <<Glass transition temperature of specific (meth)acrylic polymer (A)>> The glass transition temperature (hereinafter also referred to as "Tg") of the specific (meth)acrylic polymer (A) is less than 0°C, preferably -10°C or lower, more preferably -20°C or lower, even more preferably -30°C or lower, and particularly preferably -40°C or lower. When the glass transition temperature of the specific (meth)acrylic polymer (A) is less than 0° C., it tends to be possible to form a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating. The reason for this tendency is believed to be that the pressure-sensitive adhesive layer formed is provided with appropriate wettability. The lower limit of the glass transition temperature of the specific (meth)acrylic polymer (A) is not particularly limited, but is preferably, for example, −70° C. or higher.

[0048] The glass transition temperature of the specific (meth)acrylic polymer (A) is a value obtained by converting the absolute temperature (unit: K; the same applies below) calculated from the following formula 1 into Celsius temperature (unit: °C; the same applies below). 1 / Tg=m1 / Tg1+m2 / Tg2+ +m(k-1) / Tg(k-1)+mk / Tgk (Formula 1)

[0049] In formula 1, Tg1, Tg2, . . . , Tg(k-1), and Tgk respectively represent the glass transition temperatures expressed as absolute temperatures when each monomer constituting the specific (meth)acrylic polymer (A) is made into a homopolymer. m1, m2, . . . , m(k-1), and mk respectively represent the molar fractions of each monomer constituting the specific (meth)acrylic polymer (A), and m1 + m2 + . . . + m(k-1) + mk = 1. Note that absolute temperatures can be converted to Celsius temperatures by subtracting 273 from the absolute temperature, and Celsius temperatures can be converted to absolute temperatures by adding 273 to the Celsius temperature.

[0050] In the present disclosure, the "glass transition temperature expressed as absolute temperature when made into a homopolymer" refers to the glass transition temperature expressed as absolute temperature of a homopolymer produced by polymerizing the monomer alone. The glass transition temperature of the homopolymer was measured using a differential scanning calorimeter (DSC) [model: EXSTAR6000, manufactured by Seiko Instruments Inc.] under conditions of a nitrogen gas flow, a measurement sample of 10 mg, and a heating rate of 10°C / min, and the inflection point of the obtained DSC curve was taken as the glass transition temperature of the homopolymer.

[0051] The glass transition temperatures of representative monomers, expressed in Celsius degrees when made into homopolymers, are: 2-ethylhexyl acrylate (2EHA) -76°C, 2-ethylhexyl methacrylate (2EHMA) -10°C, n-butyl acrylate (n-BA) -57°C, n-butyl methacrylate (n-BMA) 21°C, t-butyl acrylate (t-BA) 41°C, t-butyl methacrylate (t-BMA) 107°C, i-butyl methacrylate (i-BMA) 48°C, methyl acrylate (MA) 5°C, methyl methacrylate (MMA) 103°C, isobornyl methacrylate (IBXMA) 155°C, isobornyl acrylate (IBXA) 96°C, and ethyl acrylate ( EA) at -27°C, methacrylic acid (MAA) at 185°C, 4-hydroxybutyl acrylate (4HBA) at -39°C, 2-hydroxyethyl acrylate (2HEA) at -15°C, 2-hydroxyethyl methacrylate (2HEMA) at 55°C, 2-hydroxypropyl acrylate (2HPA) at -7°C, acrylic acid (AA) at 163°C, n-octyl acrylate (n-OA) at -65°C, i-octyl acrylate (i-OA) at -75°C, i-decyl acrylate at -62°C, dimethylaminoethyl methacrylate (DM) at 18°C, ω-carboxy-polycaprolactone (n≒2) monoacrylate at -30°C, and 2-acryloyloxyethyl-succinic acid at -40°C.

[0052] The glass transition temperature of the specific (meth)acrylic polymer (A) can be appropriately adjusted, for example, by using two or more kinds of monomers having different glass transition temperatures when formed into homopolymers.

[0053] <<Weight average molecular weight of specific (meth)acrylic polymer (A)>> The weight average molecular weight (hereinafter also referred to as "Mw") of the specific (meth)acrylic polymer (A) is not particularly limited, but is, for example, preferably 400,000 to 2,000,000, more preferably 400,000 to 1,500,000, even more preferably 400,000 to 1,000,000, and particularly preferably 400,000 to 800,000. When the weight average molecular weight of the specific (meth)acrylic polymer (A) is 400,000 or more, a pressure-sensitive adhesive layer that exhibits better easy peelability at the initial stage of lamination tends to be formed. When the weight average molecular weight of the specific (meth)acrylic polymer (A) is 2,000,000 or less, there is a tendency that a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating can be formed.

[0054] The weight average molecular weight of the specific (meth)acrylic polymer (A) is a value measured by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic polymer (A) is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic polymer (A). (2) Using the film-like specific (meth)acrylic polymer (A) obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic polymer (A) in the sample solution. (3) The weight average molecular weight of the specific (meth)acrylic polymer (A) is measured in terms of standard polystyrene using gel permeation chromatography (GPC) under the following conditions.

[0055] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min

[0056] The weight average molecular weight of the specific (meth)acrylic polymer (A) can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, and the like.

[0057] <<Content of specific (meth)acrylic polymer (A)>> The content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 75 mass% to 99.75 mass%, more preferably 80 mass% to 99.7 mass%, even more preferably 80 mass% to 99 mass%, and particularly preferably 80 mass% to 98 mass%, relative to the total solid content in the pressure-sensitive adhesive composition. When the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 75 mass% or more relative to the total solid content in the pressure-sensitive adhesive composition, there is a tendency that a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating can be formed. When the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 99.75 mass% or less based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that exhibits better easy peelability at the beginning of lamination tends to be formed. Also, when the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 99.75 mass% or less based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that is less likely to lose its easy peelability over time at the beginning of lamination tends to be formed. In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.

[0058] [Specific (meth)acrylic copolymer (B)] The specific (meth)acrylic copolymer (B) contains 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, relative to all structural units, and contains a (meth)acrylic copolymer (B) having a weight average molecular weight of 10,000 to 400,000 [i.e., specific (meth)acrylic copolymer (B)]. The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000, and the content of the specific (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass per 100 parts by mass of the above-mentioned specific (meth)acrylic polymer (A).

[0059] <Structural Units Derived from Monomers Having an Organosiloxane Skeleton> The specific (meth)acrylic copolymer (B) contains 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, based on the total structural units, and the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000. In the present disclosure, the term "structural unit derived from a monomer having an organosiloxane skeleton" refers to a structural unit formed by addition polymerization of a monomer having an organosiloxane skeleton.

[0060] The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000, preferably in the range of 4,200 or more and less than 20,000, more preferably in the range of 4,500 or more and less than 20,000, and even more preferably in the range of 5,000 or more and less than 15,000. The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is, for example, less than 20,000 from the viewpoint of easy availability of the monomer having an organosiloxane skeleton. When the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is 4000 or more, it tends to be possible to form a pressure-sensitive adhesive layer in which the easy peelability at the initial stage of bonding is unlikely to be impaired over time. The reason for this tendency is thought to be that the polarity of the specific (meth)acrylic copolymer (B) is sufficiently low, and the uneven distribution of the (meth)acrylic copolymer (B) on the adhesive surface of the pressure-sensitive adhesive layer is sufficiently maintained.

[0061] In the present disclosure, the number average molecular weight of a monomer having an organosiloxane skeleton is a value measured by the following method. Specifically, it is measured according to the following (1) and (2). (1) A sample solution having a solid content of 0.2% by mass is prepared using a monomer having an organosiloxane skeleton and tetrahydrofuran. Note that the "solid content concentration" here refers to the mass ratio of the monomer having an organosiloxane skeleton in the sample solution. (2) Using gel permeation chromatography (GPC), measure the number average molecular weight of the monomer having an organosiloxane skeleton in terms of standard polystyrene under the following conditions.

[0062] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min

[0063] In addition, when the specific (meth)acrylic copolymer (B) contains two or more types of monomers having an organosiloxane skeleton with different number average molecular weights, the "number average molecular weight of the monomers having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B)" means an arithmetic average value, specifically, a value calculated by the following formula. Number average molecular weight of monomer having organosiloxane skeleton in specific (meth)acrylic copolymer (B) = [number average molecular weight of monomer 1 × amount of monomer 1 + number average molecular weight of monomer 2 × amount of monomer 2 + ··· + number average molecular weight of monomer n × amount of monomer n] / [amount of monomer 1 + amount of monomer 2 + ··· + amount of monomer n]

[0064] The type of monomer having an organosiloxane skeleton is not particularly limited, so long as the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000. A specific example of the monomer having an organosiloxane skeleton is a compound represented by the following formula (I).

[0065] [ka]

[0066] In formula (I), R 1 represents a hydrogen atom or a methyl group, and is preferably a methyl group.

[0067] In formula (I), R 2 represents a monovalent organic group. R 2 The monovalent organic group represented by the following formula (1) may be linear, branched, or cyclic. Examples of the monovalent organic group include an alkyl group, an alkenyl group, an alkynyl group, and an aryl group, and an alkyl group is preferred. R 2 When represents an alkyl group, the alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, and a t-butyl group, with a methyl group being preferred. R 2 When represents an alkenyl group, examples of the alkenyl group include a vinyl group, an allyl group, and a 2-propenyl group, and a vinyl group is preferred. R 2 When represents an alkynyl group, examples of the alkynyl group include an ethynyl group, a propargyl group, and a prop-2-yn-1-yl group, and an ethynyl group is preferable. R2 When represents an aryl group, examples of the aryl group include a phenyl group, a tolyl group, and a pyridyl group, and a phenyl group is preferable.

[0068] In formula (I), m and n each independently represent 0 or an integer of 1 or more, but m and n are not 0 at the same time. m is preferably an integer from 1 to 10, and more preferably an integer from 1 to 6. n is preferably an integer from 1 to 250, and more preferably an integer from 5 to 200, and even more preferably an integer from 10 to 200.

[0069] As the monomer having an organosiloxane skeleton, a commercially available product can be used. Examples of commercially available products of monomers having an organosiloxane skeleton include X-22-2404 (trade name, number average molecular weight: 420, manufactured by Shin-Etsu Chemical Co., Ltd.), X-22-174ASX (trade name, number average molecular weight: 1100, manufactured by Shin-Etsu Chemical Co., Ltd.), Silaplane (registered trademark) FM-0711 (trade name, number average molecular weight: 1200, manufactured by JNC Corporation), Silaplane (registered trademark) FM-0721 (trade name, number average molecular weight: 6500, manufactured by JNC Corporation), Silaplane (registered trademark) FM-0725 (trade name, number average molecular weight: 15000, manufactured by JNC Corporation), KF-2012 (trade name, number average molecular weight: 5400, manufactured by Shin-Etsu Chemical Co., Ltd.), and X-22-2426 (trade name, number average molecular weight: 13800, manufactured by Shin-Etsu Chemical Co., Ltd.). All of the above commercially available products correspond to the compound represented by formula (I).

[0070] The specific (meth)acrylic copolymer (B) may contain only one type of structural unit derived from a monomer having an organosiloxane skeleton, or may contain two or more types.

[0071] The content of the structural units derived from the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is 0.1% by mass to 10% by mass based on the total structural units of the specific (meth)acrylic copolymer (B). The content of structural units derived from monomers having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) being 0.1 mass% or more relative to the total structural units of the specific (meth)acrylic copolymer (B) means that the specific (meth)acrylic copolymer (B) actively contains structural units derived from monomers having an organosiloxane skeleton. The content of the structural units derived from the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is, for example, preferably 0.5 mass% or more, more preferably 1 mass% or more, even more preferably 2 mass% or more, and particularly preferably 3 mass% or more, relative to all structural units of the specific (meth)acrylic copolymer (B). When the content of structural units derived from a monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is 10 mass% or less relative to the total structural units of the specific (meth)acrylic copolymer (B), there is a tendency that a pressure-sensitive adhesive layer exhibiting high adhesive strength after heating can be formed. From this viewpoint, the content of the structural units derived from the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is 10 mass% or less, preferably 9 mass% or less, more preferably 8 mass% or less, and even more preferably 7 mass% or less, based on the total structural units of the specific (meth)acrylic copolymer (B).

[0072] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic copolymer (B) preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.

[0073] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.

[0074] Specific examples of the (meth)acrylic acid alkyl ester monomer are the same as those of the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic polymer (A), and therefore description thereof will be omitted here. As the (meth)acrylic acid alkyl ester monomer, for example, at least one selected from the group consisting of methyl methacrylate (MMA), n-butyl methacrylate (n-BMA), and ethyl acrylate (EA) is preferable.

[0075] When the specific (meth)acrylic copolymer (B) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, it may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or it may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.

[0076] When the specific (meth)acrylic copolymer (B) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer (B) is not particularly limited, but for example, it is preferably 50 mass% or more, more preferably 50 mass% to 99.9 mass%, even more preferably 60 mass% to 99.5 mass%, even more preferably 70 mass% to 99 mass%, even more preferably 80 mass% to 98 mass%, and particularly preferably 90 mass% to 97 mass%, relative to all structural units of the specific (meth)acrylic copolymer (B). Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic copolymer (B) means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic copolymer (B).

[0077] <Other building blocks> The specific (meth)acrylic copolymer (B) may contain structural units (so-called other structural units) other than the above-mentioned structural units, i.e., the structural units derived from monomers having an organosiloxane skeleton, which are essential structural units, and the structural units derived from (meth)acrylic acid alkyl ester monomers, which are optional structural units, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0078] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.

[0079] When the specific (meth)acrylic copolymer (B) contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.

[0080] When the specific (meth)acrylic copolymer (B) contains other structural units, the content of the other structural units in the specific (meth)acrylic copolymer (B) is not particularly limited and can be appropriately set depending on the purpose as long as the effect of the pressure-sensitive adhesive composition of the present disclosure is not impaired.

[0081] <<Glass transition temperature of specific (meth)acrylic copolymer (B)>> The glass transition temperature of the specific (meth)acrylic copolymer (B) is not particularly limited, but is, for example, preferably from 20°C to 50°C, more preferably from 20°C to 45°C, and even more preferably from 20°C to 40°C.

[0082] The glass transition temperature of the specific (meth)acrylic copolymer (B) was measured using a differential scanning calorimeter (DSC) in a nitrogen gas flow using 8 mg of a measurement sample under conditions of a measurement start temperature of -70°C, a measurement end temperature of 150°C, and a heating rate of 10°C / min, and the inflection point of the obtained DSC curve was taken as the glass transition temperature of the specific (meth)acrylic copolymer (B). As a differential scanning calorimeter, for example, DSC2500 (model number) manufactured by TA Instruments Co., Ltd. can be suitably used. However, the differential scanning calorimeter is not limited to this.

[0083] The glass transition temperature of the specific (meth)acrylic copolymer (B) can be appropriately adjusted, for example, by using two or more kinds of monomers having different glass transition temperatures when formed into homopolymers.

[0084] <<Weight average molecular weight of specific (meth)acrylic copolymer (B)>> The weight average molecular weight of the specific (meth)acrylic copolymer (B) is 10,000 to 400,000. When the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 10,000 or more, there is a tendency that a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating can be formed. From this viewpoint, the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 10,000 or more, preferably 20,000 or more, more preferably 30,000 or more, even more preferably 50,000 or more, and particularly preferably 70,000 or more. When the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, a pressure-sensitive adhesive layer that exhibits easy peelability at the initial stage of lamination tends to be formed. Also, when the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, a pressure-sensitive adhesive layer that is unlikely to lose its easy peelability at the initial stage of lamination over time tends to be formed. From this viewpoint, the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, preferably 350,000 or less, more preferably 300,000 or less, even more preferably 250,000 or less, and particularly preferably 200,000 or less.

[0085] The weight average molecular weight of the specific (meth)acrylic copolymer (B) is measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.

[0086] The weight average molecular weight of the specific (meth)acrylic copolymer (B) can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, and the like.

[0087] <<Content of specific (meth)acrylic copolymer (B)>> The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 21 parts by mass relative to 100 parts by mass of the specific (meth)acrylic polymer (A). The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure being 0.1 part by mass or more per 100 parts by mass of the specific (meth)acrylic polymer (A) means that the pressure-sensitive adhesive composition of the present disclosure actively contains the specific (meth)acrylic copolymer (B). The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is, for example, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, relative to 100 parts by mass of the specific (meth)acrylic polymer (A). When the content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 21 parts by mass or less per 100 parts by mass of the specific (meth)acrylic polymer (A), a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating tends to be formed. From such a viewpoint, the content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 21 parts by mass or less, preferably 18 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less, relative to 100 parts by mass of the specific (meth)acrylic polymer (A).

[0088] [Method for producing specific (meth)acrylic polymer] The method for producing the specific (meth)acrylic polymer (A) and the specific (meth)acrylic copolymer (B) [i.e., the specific (meth)acrylic polymer] is not particularly limited. The specific (meth)acrylic polymer can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.

[0089] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and the mixture is heated and reacted for several hours with stirring at the reflux temperature of the organic solvent in a nitrogen stream. In this case, at least a portion of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively.

[0090] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.

[0091] In producing the specific (meth)acrylic polymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic polymer, ease of polymerization reaction, and the like.

[0092] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.

[0093] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic polymer, it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.

[0094] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.

[0095] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.

[0096] In producing the specific (meth)acrylic polymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.

[0097] When a chain transfer agent is used in producing the specific (meth)acrylic polymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.

[0098] The polymerization temperature is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.

[0099] [Specific silicone compounds (C)] The pressure-sensitive adhesive composition of the present disclosure has at least one of an epoxy group and a polyether group in a side chain, and has a kinetic viscosity of 2000 mm at 25° C. 2 / s or less [i.e., specific silicone compound (C)]. The content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 10 parts by mass relative to 100 parts by mass of the above-mentioned specific (meth)acrylic polymer (A).

[0100] The structure of the specific silicone compound (C) is not particularly limited as long as it is a compound having a siloxane bond as the main skeleton and at least one of an epoxy group and a polyether group in the side chain.

[0101] The specific silicone compound (C) is preferably, for example, a compound having a group represented by the following formula (a) on the side chain.

[0102] [ka]

[0103] In formula (a), R a represents a chain aliphatic group. R a The chain aliphatic group represented by the formula (I) may be a linear aliphatic group or a branched aliphatic group. R a The chain aliphatic group represented by the following formula (I) preferably has 1 to 18 carbon atoms.

[0104] R a Examples of the chain aliphatic group represented by the formula (I) include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, an octylene group, a decylene group, a dodecylene group, a vinylene group, an ethylidene group, a vinylidene group, a propenylene group, and a butadienylene group. Among these, R a The chain aliphatic group represented by the following formula (I) is preferably a substituent selected from alkylene groups such as a methylene group, an ethylene group, a propylene group, and a butylene group.

[0105] The specific silicone compound (C) is preferably, for example, a compound represented by the following formula (1).

[0106] [ka]

[0107] In formula (1), R 1a each independently represents a monovalent hydrocarbon group having 1 to 18 carbon atoms; R 1b each independently represents a group represented by formula (a), m represents 0 or an integer of 1 or more, and n represents an integer of 1 or more.

[0108] In formula (1), R 1a The monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the following formula may be substituted or unsubstituted. In formula (1), R 1a The monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (I) preferably contains at least one type of hydrocarbon group selected from the group consisting of monovalent aliphatic hydrocarbon groups having 1 to 18 carbon atoms, monovalent alicyclic hydrocarbon groups having 1 to 18 carbon atoms, and monovalent aromatic hydrocarbon groups having 1 to 18 carbon atoms.

[0109] Specific examples of monovalent aliphatic hydrocarbon groups having 1 to 18 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an s-butyl group, an i-butyl group, a t-butyl group, a pentyl group, a hexyl group, an octyl group, a decyl group, a dodecyl group, an allyl group, and a vinyl group. The monovalent aliphatic hydrocarbon group having 1 to 18 carbon atoms may be the above aliphatic hydrocarbon group substituted with a substituent such as an alkyl group, an alkoxy group, an aryl group, an amino group, a halogen atom, a methacryloxy group, a mercapto group, an imino group or a ureido group.

[0110] Specific examples of the monovalent alicyclic hydrocarbon group having 1 to 18 carbon atoms include a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclopentenyl group, and a cyclohexenyl group. The monovalent alicyclic hydrocarbon group having 1 to 18 carbon atoms may be the above alicyclic hydrocarbon group substituted with a substituent such as an alkyl group, an alkoxy group, an aryl group, an aryloxy group, an amino group, a halogen atom, a methacryloxy group, a mercapto group, an imino group or a ureido group.

[0111] Specific examples of monovalent aromatic hydrocarbon groups having 1 to 18 carbon atoms include aryl groups such as a phenyl group and a tolyl group, alkyl group-substituted aryl groups such as a methylphenyl group, a dimethylphenyl group, an ethylphenyl group, a butylphenyl group, and a t-butylphenyl group, and alkoxy group-substituted aryl groups such as a methoxyphenyl group, an ethoxyphenyl group, a butoxyphenyl group, and a t-butoxyphenyl group. The monovalent aromatic hydrocarbon group having 1 to 18 carbon atoms may be the above aromatic hydrocarbon group substituted with a substituent such as an alkyl group, an alkoxy group, an aryl group, an aryloxy group, an amino group, a halogen atom, a methacryloxy group, a mercapto group, an imino group or a ureido group.

[0112] In formula (1), R 1a The monovalent hydrocarbon group having 1 to 18 carbon atoms and represented by the formula (I) is preferably a monovalent hydrocarbon group selected from an alkyl group and an aryl group, and more preferably an alkyl group such as a methyl group, an ethyl group, an n-propyl group, an i-isopropyl group, an n-butyl group, an s-butyl group, an i-butyl group, a t-butyl group, an octyl group, a cyclohexyl group, an epoxycyclohexylethyl group, a glycidoxypropyl group, a chloropropyl group, a methacryloxypropyl group, a mercaptopropyl group, an aminopropyl group, an N-phenylaminopropyl group, an N-aminopropyl group, or a ureidopropyl group; or an aryl group such as a phenyl group, a p-tolyl group, an m-tolyl group, an o-tolyl group, a p-methoxyphenyl group, an m-methoxyphenyl group, or an o-methoxyphenyl group.

[0113] In formula (1), m is preferably 0 or an integer of 1-100. In formula (1), n ​​is preferably an integer of 1-100.

[0114] An example of a commercially available specific silicone compound (C) represented by formula (1) is KF-101 (trade name, kinematic viscosity at 25° C.: 1500 mm 2 / s, Shin-Etsu Chemical Co., Ltd.], X-22-343 [trade name, kinematic viscosity at 25°C: 25mm 2 / s, Shin-Etsu Chemical Co., Ltd.], and X-22-2000 (trade name, kinematic viscosity at 25°C: 190 mm 2 / s, manufactured by Shin-Etsu Chemical Co., Ltd.

[0115] The specific silicone compound (C) is preferably, for example, a compound represented by the following formula (2).

[0116] [ka]

[0117] In formula (2), R 2a each independently represents a monovalent hydrocarbon group having 1 to 18 carbon atoms; R 2b each independently represents a group represented by formula (a), R 2c represents a monovalent organic group having a polyether group, p represents 0 or an integer of 1 or more, q represents an integer of 1 or more, and r represents an integer of 1 or more.

[0118] In formula (2), R 2a The monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the following formula may be substituted or unsubstituted. In formula (2), R 2a The monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (I) preferably contains at least one type of hydrocarbon group selected from the group consisting of monovalent aliphatic hydrocarbon groups having 1 to 18 carbon atoms, monovalent alicyclic hydrocarbon groups having 1 to 18 carbon atoms, and monovalent aromatic hydrocarbon groups having 1 to 18 carbon atoms.

[0119] Specific examples of the monovalent aliphatic hydrocarbon group having 1 to 18 carbon atoms, the monovalent alicyclic hydrocarbon group having 1 to 18 carbon atoms, and the monovalent aromatic hydrocarbon group having 1 to 18 carbon atoms in formula (2) are the same as the specific examples of the monovalent aliphatic hydrocarbon group having 1 to 18 carbon atoms, the monovalent alicyclic hydrocarbon group having 1 to 18 carbon atoms, and the monovalent aromatic hydrocarbon group having 1 to 18 carbon atoms in formula (1) described above, and therefore description thereof will be omitted here.

[0120] In addition, in formula (2), R 2a Preferred examples of the monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (1) are 1a Since these are the same as the preferred examples of the monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the following formula, description thereof will be omitted here.

[0121] In formula (2), p is preferably 0 or an integer of 1-100. In formula (2), q is preferably an integer of 1-100. In formula (2), r is preferably an integer of 1-100.

[0122] In formula (2), R 2c The monovalent organic group having a polyether group represented by the following formula (b) is preferably an organic group represented by the following formula (b).

[0123] [ka]

[0124] In formula (b), R 3 each independently represents a divalent hydrocarbon group having 1 to 18 carbon atoms; R 4 each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 18 carbon atoms, and s represents an integer of 2 or greater.

[0125] In formula (b), R 3The divalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (I) preferably contains at least one type of hydrocarbon group selected from the group consisting of divalent aliphatic hydrocarbon groups having 1 to 18 carbon atoms, divalent alicyclic hydrocarbon groups having 1 to 18 carbon atoms, and divalent aromatic hydrocarbon groups having 1 to 18 carbon atoms.

[0126] Specific examples of divalent aliphatic hydrocarbon groups having 1 to 18 carbon atoms include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, an octylene group, a decylene group, a dodecylene group, a vinylene group, an ethylidene group, a vinylidene group, a propenylene group, and a butadienylene group. Specific examples of the divalent alicyclic hydrocarbon group having 1 to 18 carbon atoms include a cyclopentylene group, a cyclohexylene group, a cycloheptylene group, a cyclopentenylene group, a cyclohexenylene group, and a cyclohexylidene group. Specific examples of the divalent aromatic hydrocarbon group having 1 to 18 carbon atoms include a phenylene group, a biphenylene group, and a terphenylene group.

[0127] In formula (b), R 3 The divalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (I) is preferably a divalent hydrocarbon group selected from an alkylene group and an arylene group, more preferably a divalent hydrocarbon group selected from an alkylene group such as a methylene group, an ethylene group, a propylene group, or a butylene group, and even more preferably a divalent hydrocarbon group selected from an ethylene group and a propylene group. That is, in formula (2), R 2c The monovalent organic group having a polyalkylene ether group represented by the formula (c) is preferably a monovalent organic group containing at least one repeating unit represented by the following formula (c) or (d).

[0128] [ka]

[0129] In formula (c), t represents an integer of 2 or more.

[0130] [ka]

[0131] In formula (d), u represents an integer of 2 or more.

[0132] In the formula (c), t is preferably an integer of 2-100. In the formula (d), u is preferably an integer of 2-100.

[0133] In formula (b), R 4 Preferred examples of the monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the formula (1) are 1a Since these are the same as the preferred examples of the monovalent hydrocarbon group having 1 to 18 carbon atoms represented by the following formula, description thereof will be omitted here.

[0134] In the formula (b), s is preferably an integer of 2-100.

[0135] An example of a commercially available specific silicone compound (C) represented by formula (2) is X-22-4741 (trade name, kinematic viscosity at 25° C.: 350 mm 2 / s, manufactured by Shin-Etsu Chemical Co., Ltd.), DOWSIL (registered trademark) BY16-869 (trade name, kinematic viscosity at 25°C: 1000 mm 2 / s, manufactured by Dow Toray Co., Ltd.], DOWSIL (registered trademark) BY16-870 (trade name, kinematic viscosity at 25°C: 550 mm 2 / s, manufactured by Dow Toray Co., Ltd.], DOWSIL (registered trademark) BY16-760 (trade name, kinematic viscosity at 25°C: 1500 mm 2 / s, manufactured by Dow Toray Industries, Inc.

[0136] The specific silicone compound (C) is preferably, for example, a compound represented by the following formula (3).

[0137] [ka]

[0138] In formula (3), p is the repeating number of dimethylsiloxane structural units and is 0 or an integer from 1 to 100, q is the repeating number of methylpropylenesiloxane structural units having a polyethylene oxide chain and is an integer from 2 to 100, and a is the repeating number of ethylene oxide structural units and is an integer from 2 to 100. When the compound represented by formula (3) is an aggregate of a plurality of compounds, p, q, and a are average values ​​of the aggregate of the compounds and are rational numbers.

[0139] In formula (3), the repeating number of the ethylene oxide structural unit represented by a is preferably an integer of 10-100. In formula (3), the repeating number of the dimethylsiloxane structural unit represented by p is preferably an integer of 1-80. In formula (3), the repeating number of the methylpropylenesiloxane structural unit represented by q is preferably an integer of 2-80.

[0140] An example of a commercially available product of the specific silicone compound (C) represented by formula (3) is DOWSIL (registered trademark) FZ-2110 (trade name, kinematic viscosity at 25° C.: 130 mm 2 / s, Dow Toray Industries, Inc.], and DOWSIL (registered trademark) L-7002 (trade name, kinematic viscosity at 25°C: 1200 mm 2 / s, manufactured by Dow Toray Co., Ltd. Examples include:

[0141] The kinetic viscosity of the specific silicone compound (C) at 25°C is 2000mm 2 / s or less, 1900mm 2 / s or less is preferable, and 1800 mm 2 / s or less is more preferable, and 1700 mm 2 / s or less is more preferable, and 1600 mm 2 It is particularly preferable that the ratio is equal to or less than 1 / s. The specific silicone compound (C) has a kinetic viscosity of 2000 mm at 25°C. 2 / s or less, there is a tendency that an adhesive layer exhibiting high adhesive strength after heating can be formed. The lower limit of the kinetic viscosity of the specific silicone compound (C) at 25° C. is not particularly limited, but is, for example, 5 mm 2 / s or more is preferable, and 10 mm 2 / s or more is preferable, and 15 mm 2 More preferably, it is 20 mm / s or more. 2 It is particularly preferable that the ratio is 1 / s or more.

[0142] The kinetic viscosity of the specific silicone compound (C) at 25° C. is a value measured using a capillary viscometer in accordance with a method in accordance with JIS K7367-1:2002.

[0143] The weight average molecular weight of the specific silicone compound (C) is not particularly limited, but is, for example, preferably 150,000 or less, more preferably 100,000 or less, even more preferably 80,000 or less, and particularly preferably 60,000 or less. The lower limit of the weight average molecular weight of the specific silicone compound (C) is not particularly limited, but is preferably, for example, 1,000 or more.

[0144] The weight average molecular weight of the specific silicone compound (C) is a value measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.

[0145] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of specific silicone compound (C), or may contain two or more types.

[0146] The content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 10 parts by mass relative to 100 parts by mass of the specific (meth)acrylic polymer (A). The content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure being 0.1 part by mass or more per 100 parts by mass of the specific (meth)acrylic polymer (A) means that the pressure-sensitive adhesive composition of the present disclosure actively contains the specific silicone compound (C). The content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure is, for example, preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 mass% or more, relative to 100 parts by mass of the specific (meth)acrylic polymer (A). When the content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure is, for example, 10 parts by mass or less per 100 parts by mass of the specific (meth)acrylic polymer (A), a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating tends to be formed. From such a viewpoint, the content of the specific silicone compound (C) in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass or less, preferably 8 parts by mass or less, more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less, per 100 parts by mass of the specific (meth)acrylic polymer (A).

[0147] [Crosslinking Agent] The pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent. The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent. Among these, the crosslinking agent is preferably an isocyanate-based crosslinking agent or a metal chelate-based crosslinking agent, and more preferably an isocyanate-based crosslinking agent.

[0148] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.

[0149] The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.

[0150] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).

[0151] The type of the epoxy crosslinking agent is not particularly limited. Specific examples of epoxy crosslinking agents include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol di ... Examples of such glycidyl ethers include glycerol polyglycidyl ether, resorcinol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, tris(glycidyl)isocyanurate, tris(glycidoxyethyl)isocyanurate, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine).

[0152] As the epoxy crosslinking agent, a commercially available product can be used. Examples of commercially available epoxy crosslinking agents include "TETRAD (registered trademark)-X" and "TETRAD (registered trademark)-C" (both manufactured by Mitsubishi Gas Chemical Company, Inc.).

[0153] The type of the metal chelate crosslinking agent is not particularly limited. Examples of metal chelate crosslinking agents include aluminum chelate compounds such as aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum tris(ethylacetoacetate), and aluminum tris(acetylacetonate), titanium chelate compounds, zirconium chelate compounds, and cobalt chelate compounds.

[0154] As the metal chelate crosslinking agent, commercially available products can be used. Examples of commercially available metal chelate crosslinking agents include Aluminum Chelate A (trade name: aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd.), Aluminum Chelate D (trade name: aluminum monoacetylacetonate bis(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.), and ALCH-TR (trade name: aluminum tris(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.).

[0155] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of crosslinking agent, or may contain two or more types.

[0156] The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 0.05 parts by mass to 10 parts by mass, more preferably 0.1 parts by mass to 5 parts by mass, even more preferably 0.1 parts by mass to 3 parts by mass, still more preferably 0.1 parts by mass to 1 part by mass, and particularly preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic polymer (A). When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer can be formed in which the easy peelability at the initial stage of bonding is less likely to be impaired over time. When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating can be formed.

[0157] <<Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)>> The ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)] is not particularly limited, but is, for example, preferably 0.001 to 0.1, more preferably 0.001 to 0.08, further preferably 0.001 to 0.05, and particularly preferably 0.001 to 0.03. When the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.001 or more, a pressure-sensitive adhesive layer that exhibits better easy peelability at the beginning of lamination tends to be formed. Also, when the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.001 or more, a pressure-sensitive adhesive layer that is less likely to lose its easy peelability over time at the beginning of lamination tends to be formed. When the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.1 or less, a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating tends to be formed.

[0158] In the present disclosure, the term "crosslinkable functional group in the crosslinking agent" means a functional group possessed by the crosslinking agent and capable of undergoing a crosslinking reaction with the crosslinkable functional group in the specific (meth)acrylic polymer (A). For example, when the crosslinking agent is an isocyanate-based crosslinking agent, it means an isocyanate group, and when the crosslinking agent is an epoxy crosslinking agent, it means an epoxy group.

[0159] In the present disclosure, the number of moles of a crosslinkable functional group means the total number of moles of all crosslinkable functional groups when there are multiple crosslinkable functional groups.

[0160] The ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)] can be calculated by the following formulas (1) to (3).

[0161] Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = [Content of crosslinkable functional group in crosslinker (unit: mass%) / solid content concentration of crosslinker (unit: mass%) × blend amount of crosslinker [amount as solid content] (unit: g)] / chemical formula weight of crosslinkable functional group (unit: g / mol) × 1000 (1)

[0162] Number of moles of crosslinkable functional groups in specific (meth)acrylic polymer (A) [unit: mmol] = [Content of the structural unit derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) (unit: mass%) / 100 × blend amount of the specific (meth)acrylic polymer (A) (unit: g) / molecular weight of the structural unit derived from the monomer having a crosslinkable functional group (unit: g / mol) × number of crosslinkable functional groups (valence) in the structural unit derived from the monomer having a crosslinkable functional group × 1000] (2)

[0163] Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) = Value obtained by formula (1) / Value obtained by formula (2) (3)

[0164] In addition, when the crosslinking agent is a metal chelate-based crosslinking agent, for example, the crosslinkable functional group contained in the specific (meth)acrylic polymer (A) forms a coordinate bond with a central metal in a metal chelate compound that is a metal chelate-based crosslinking agent, and therefore, by replacing the valence of the central metal with the number of functional groups, the number of moles of the crosslinkable functional groups in the crosslinking agent used for calculating the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) can be obtained. For example, since the valence of the central metal in an aluminum chelate compound, which is a metal chelate crosslinking agent, is 3, the calculation can be performed by replacing the aluminum chelate compound with one having 3 moles of functional groups per mole.

[0165] When the crosslinking agent is a metal chelate crosslinking agent, the molar number of crosslinkable functional groups in the crosslinking agent is calculated by the following calculation formula (4). When the crosslinking agent is a metal chelate crosslinking agent, the ratio of the molar number of crosslinkable functional groups in the crosslinking agent to the molar number of crosslinkable functional groups in the specific (meth)acrylic polymer (A) can be calculated by replacing the value calculated by calculation formula (1) in the above formula (3) with the value calculated by calculation formula (4) below. Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = A × B / C × 1000 (4) A = valence of the metal in the metal chelate crosslinker B = amount of metal chelate crosslinking agent (amount as solid content) (unit: g) C = molecular weight of metal chelate crosslinker (unit: g / mol)

[0166] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be improved. As the organic solvent, for example, the same organic solvents as those used in the polymerization reaction of the above-mentioned specific (meth)acrylic polymer can be mentioned.

[0167] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.

[0168] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be appropriately set depending on the purpose.

[0169] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the specific (meth)acrylic polymer, crosslinking catalysts, tackifiers, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.

[0170] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components can be appropriately set within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0171] <Gel fraction after crosslinking> The gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present disclosure (so-called gel fraction of the pressure-sensitive adhesive layer) is not particularly limited, but is, for example, preferably 50 mass% or more, more preferably 50 mass% to 90 mass%, and even more preferably 50 mass% to 85 mass%. The adhesive composition of the present disclosure, when the gel fraction after crosslinking is 50% by mass or more, tends to be able to form an adhesive layer that exhibits better easy peelability at the beginning of lamination. Also, the adhesive composition of the present disclosure, when the gel fraction after crosslinking is 50% by mass or more, tends to be able to form an adhesive layer whose easy peelability at the beginning of lamination is less likely to be impaired over time.

[0172] In the present disclosure, the "gel fraction of the pressure-sensitive adhesive composition after crosslinking" refers to the proportion of solvent-insoluble matter measured using ethyl acetate as an extraction solvent. Specifically, the gel fraction of the pressure-sensitive adhesive composition after crosslinking is measured according to the following (1) to (4). (1) About 0.15 g of the crosslinked adhesive composition (i.e., adhesive layer) is attached to a 250-mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer facing inward to prevent leakage of the gel, to prepare a sample. The mass is then accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) Take out the sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, measure the mass accurately using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).

[0173] <Application> The application of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited. The pressure-sensitive adhesive composition of the present disclosure exhibits easy peelability at the initial stage of bonding, and this easy peelability is unlikely to be lost over time. Moreover, after heating, a pressure-sensitive adhesive layer exhibiting high adhesive strength can be formed, and therefore, for example, the pressure-sensitive adhesive composition of the present disclosure is suitable for use in bonding a display and an optical member.

[0174] [Adhesive sheet] The pressure-sensitive adhesive sheet of the present disclosure includes a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure. The pressure-sensitive adhesive sheet of the present disclosure has an adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure described above, and therefore exhibits easy releasability at the initial stage of attachment, and this easy releasability is unlikely to be lost over time, and exhibits high adhesive strength after heating. The adherend to which the pressure-sensitive adhesive sheet of the present disclosure is applied is not particularly limited, but is preferably, for example, a display or an optical member.

[0175] The pressure-sensitive adhesive sheet of the present disclosure may be a substrate-free pressure-sensitive adhesive sheet that does not have a substrate, or a substrate-containing pressure-sensitive adhesive sheet that has a pressure-sensitive adhesive layer on one or both sides of a substrate. In the pressure-sensitive adhesive sheet of the present disclosure, the exposed surface of the pressure-sensitive adhesive layer may be protected by a release film.

[0176] The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive sheet is put to practical use, and is peeled off at the time of use.

[0177] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is generally from 1 μm to 100 μm, preferably from 3 μm to 50 μm, and more preferably from 5 μm to 30 μm.

[0178] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.

[0179] When the pressure-sensitive adhesive sheet of the present disclosure includes a substrate, the substrate is not particularly limited. Examples of the substrate include films containing resins such as polyolefin resins (e.g., polyethylene and polypropylene), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.

[0180] The surface of the substrate on which the adhesive layer is provided may be subjected to a surface treatment such as corona discharge treatment or plasma discharge treatment (so-called adhesion enhancing treatment) in order to improve adhesion between the substrate and the adhesive layer.

[0181] The substrate may contain various additives, such as plasticizers, colorants (eg, dyes and pigments), heat stabilizers, light stabilizers, antistatic agents, flame retardants, antioxidants, and the like. The substrate may be partially or entirely patterned.

[0182] The thickness of the substrate is not particularly limited, but is generally 10 μm to 500 μm, preferably 10 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 10 μm to 100 μm.

[0183] "Substrate thickness" in this disclosure means the average thickness of the substrate. The average thickness of the substrate is a value measured by a method conforming to the above-mentioned method for measuring the average thickness of the pressure-sensitive adhesive layer.

[0184] [How to make adhesive sheets] The method for producing the pressure-sensitive adhesive sheet of the present disclosure is not particularly limited. The pressure-sensitive adhesive sheet of the present disclosure can be produced by known methods. The pressure-sensitive adhesive sheet of the present disclosure can be produced, for example, by the following method. In the case of a substrate-free type adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film.Then, the formed coating film is dried to form an adhesive film on the release film.Then, the exposed surface of the formed adhesive film is laminated and bonded to the easy-release treated surface of a separately prepared release film, and then cured to produce a substrate-free type adhesive sheet having a laminated structure of release film / adhesive layer / release film.

[0185] In the case of a substrate-type adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-adhesion treated surface of the substrate to form a coating film on the substrate. Then, the formed coating film is dried to form an adhesive film on the substrate. Then, the exposed surface of the formed adhesive film is laminated on the easy-release treated surface of the release film, and then cured to produce a substrate-type adhesive sheet having a laminated structure of release film / adhesive layer / substrate.

[0186] As another method, for example, the following method can be mentioned. The adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then laminated to the easy-adhesion treated surface of a substrate, and then cured to produce a substrate-type adhesive sheet having a laminated structure of substrate / adhesive layer / release film.

[0187] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.

[0188] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.

[0189] The curing is carried out, for example, for 2 to 7 days in an environment with an atmospheric temperature of 20° C. to 50° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH).

[0190] [Optical components] The optical member of the present disclosure includes a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure. The optical member of the present disclosure has a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure described above, and therefore exhibits easy releasability at the initial stage of attachment, and this easy releasability is unlikely to be lost over time, and exhibits high adhesive strength after heating. The adherend to which the optical member of the present disclosure is attached is not particularly limited, but is preferably, for example, another optical member or a display.

[0191] The optical member is not particularly limited, and examples thereof include members constituting devices such as image display devices and input devices (so-called optical devices) and members used in these devices. Specific examples of optical components include polarizing plates, AG (Anti-Glare) polarizing plates, wave plates, retardation plates including 1 / 2, 1 / 4 and other wave plates, viewing angle compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, transparent conductive films such as ITO (Indium-Tin Oxide) films, prism sheets, lens sheets, and diffusion plates. Examples of materials for optical components include polyolefin resins (e.g., polyethylene resins and polyester resins), acetate resins (e.g., triacetyl cellulose resins), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine resins. EXAMPLES

[0192] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.

[0193] [Production of (meth)acrylic polymer A] [Manufacturing example A-1] A reactor equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 116.0 parts by mass of ethyl acetate (organic solvent for polymerization). Next, 100.0 parts by mass of a monomer mixture consisting of 93.0 parts by mass of n-butyl acrylate (n-BA) and 7.0 parts by mass of 2-hydroxyethyl acrylate (2HEA) was prepared in another container. 20% by mass of the prepared monomer mixture was charged into the reactor, and then heated and refluxed at reflux temperature for 10 minutes. Next, under reflux temperature conditions, the remaining 80% by mass of the monomer mixture, 45.0 parts by mass of ethyl acetate (organic solvent for polymerization), and 0.026 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] were successively dropped into the reactor over 120 minutes, and the reaction was allowed to proceed for 30 minutes after the completion of the dropping, completing the reaction. After completion of the reaction, the solution was diluted with ethyl acetate so that the solid content concentration became 32.0% by mass, thereby obtaining a solution of (meth)acrylic polymer A-1.

[0194] The term "solids concentration" used herein means the mass proportion of the (meth)acrylic polymer A-1 in the solution of the (meth)acrylic polymer A-1. The same applies to each of the solutions of the (meth)acrylic polymers A-2 to A-6 described below.

[0195] [Manufacturing examples A-2 to A-6] In Production Examples A-2 to A-6, the monomer composition of the (meth)acrylic polymer was changed to the monomer composition shown in Table 1, and the weight average molecular weight of the (meth)acrylic polymer was adjusted to the weight average molecular weight shown in Table 1 by adjusting at least one of the amount of the organic solvent used and the amount of the polymerization initiator used. Except for this, the same operation as in Production Example A-1 was performed to obtain solutions of (meth)acrylic polymers A-2 to A-6 each having a solid content concentration of 32.0 mass%.

[0196] The monomer compositions (unit: mass%) of the (meth)acrylic polymers A-1 to A-6, the glass transition temperatures (Tg, unit: °C) of the (meth)acrylic polymers A-1 to A-6, and the weight average molecular weights (Mw, unit: 10,000 (in the table, "×10") of the (meth)acrylic polymers A-1 to A-6 are shown. 4 " are shown in Table 1.

[0197] The glass transition temperatures of the (meth)acrylic polymers A-1 to A-6 were calculated in the same manner as the above-mentioned calculation method for the glass transition temperature of the specific (meth)acrylic polymer (A). The weight average molecular weights of the (meth)acrylic polymers A-1 to A-6 were measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.

[0198] Of the (meth)acrylic polymers A-1 to A-6 obtained above, the (meth)acrylic polymers A-1 to A-4 correspond to the specific (meth)acrylic polymer (A) in the present disclosure.

[0199] [Table 1]

[0200] Details of each monomer listed in Table 1 are as follows. <(Meth)acrylic acid alkyl ester monomer> "n-BA" n-butyl acrylate "MA" Methyl acrylate "2EHA" 2-Ethylhexyl acrylate <Monomers having crosslinkable functional groups> "2HEA" 2-Hydroxyethyl acrylate [Cross-linkable functional group: hydroxyl group, molecular weight: 116] "AA" acrylic acid [Crosslinkable functional group: carboxy group, molecular weight: 72]

[0201] In Table 1, "-" in the monomer composition column means that the monomer in that column was not used.

[0202] [Production of (meth)acrylic copolymer B] [Manufacturing example B-1] A reaction apparatus equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 45.0 parts by mass of ethyl acetate (organic solvent for polymerization). Next, in another container, a solution consisting of 45.0 parts by mass of methyl methacrylate (MMA), 25.0 parts by mass of n-butyl methacrylate (n-BMA), 29.0 parts by mass of ethyl acrylate (EA; glass transition temperature when homopolymerized is −27° C.), 1.0 parts by mass of a monomer having an organosiloxane skeleton [trade name: KF-2012, number average molecular weight: 5400, manufactured by Shin-Etsu Chemical Co., Ltd.], 0.4 parts by mass of 2,2′-azobis(isobutyric acid) dimethyl [polymerization initiator], and 35.0 parts by mass of ethyl acetate (organic solvent for polymerization) was prepared. The prepared solution was successively dropped into the reaction apparatus over 180 minutes under reflux temperature conditions, and after the end of the dropping, the reaction was allowed to proceed for 180 minutes, and the reaction was completed. After completion of the reaction, the solution was diluted with ethyl acetate to a solid content of 48.0% by mass, to obtain a solution of (meth)acrylic copolymer B-1.

[0203] The term "solid content concentration" used herein means the mass proportion of the (meth)acrylic copolymer B-1 in the solution of the (meth)acrylic copolymer B-1. The same applies to each of the solutions of the following (meth)acrylic copolymers B-2 to B-14.

[0204] [Manufacturing examples B-2 to B-14] In Production Examples B-2 to B-14, the monomer composition of the (meth)acrylic copolymer was changed to the monomer composition shown in Table 2, and the weight average molecular weight of the (meth)acrylic copolymer was adjusted to the weight average molecular weight shown in Table 2 by adjusting at least one of the amount of organic solvent used and the amount of polymerization initiator used. Except for this, the same operation as in Production Example B-1 was performed to obtain solutions of (meth)acrylic copolymers B-2 to B-14 each having a solid content concentration of 48.0 mass%.

[0205] The monomer compositions (unit: mass%) of the (meth)acrylic copolymers B-1 to B-14, the number average molecular weights (Mn) of the monomers having an organosiloxane skeleton in the (meth)acrylic copolymers B-1 to B-14, and the weight average molecular weights (Mw, unit: 10,000 (in the table, "×10 4 " are shown in Table 2.

[0206] The number average molecular weights of the monomers having an organosiloxane skeleton in the (meth)acrylic copolymers B-1 to B-14 were calculated in the same manner as the number average molecular weight of the monomers having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) described above. The weight average molecular weights of the (meth)acrylic copolymers B-1 to B-14 were measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.

[0207] Of the (meth)acrylic copolymers B-1 to B-14 obtained above, the (meth)acrylic copolymers B-1 to B-7 correspond to the specific (meth)acrylic copolymer (B) in the present disclosure.

[0208] [Table 2]

[0209] Details of each monomer listed in Table 2 are as follows. <(Meth)acrylic acid alkyl ester monomer> "MMA": Methyl methacrylate "n-BMA": n-butyl methacrylate "EA": Ethyl acrylate

[0210] <Monomer having an organosiloxane skeleton> "KF-2012" (trade name, number average molecular weight: 5400, compound represented by formula (I), manufactured by Shin-Etsu Chemical Co., Ltd.) "X-22-2426" (trade name, number average molecular weight: 13800, compound represented by formula (I), manufactured by Shin-Etsu Chemical Co., Ltd.) "FM-0711" [Product name: Silaplane (registered trademark) FM-0711, number average molecular weight: 1200, manufactured by JNC Corporation]

[0211] In Table 2, "-" in the monomer composition column means that the monomer in that column was not used.

[0212] [Preparation of Adhesive Composition] Example 1 A mixture of 100 parts by mass (solid content equivalent) of a solution of a (meth)acrylic polymer A-1, 8 parts by mass (solid content equivalent) of a solution of a (meth)acrylic copolymer B-1, and a silicone compound having an epoxy group on the side chain (trade name: KF-101, kinetic viscosity at 25°C: 1500 mm 2 2 parts by mass of a copolymer of 1,2-diisocyanate and 1,2-diisocyanate copolymer (manufactured by Shin-Etsu Chemical Co., Ltd.) and 0.4 parts by mass (solid content equivalent) of a crosslinking agent (trade name: Takenate (registered trademark) D-110N, xylylene diisocyanate (XDI) compound, solid content concentration: 75% by mass, manufactured by Mitsui Chemicals, Inc.) were thoroughly mixed to obtain a pressure-sensitive adhesive composition of Example 1. In the obtained pressure-sensitive adhesive composition, the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1 [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1] was 0.025.

[0213] The ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the (meth)acrylic polymer A-1 was calculated in the same manner as the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A). Specifically, it was calculated as follows. Note that Takenate (registered trademark) D-110N, which is an isocyanate-based crosslinking agent, has a solid content of 75% by mass and an isocyanate group content of 11.5% by mass. The chemical formula weight of the isocyanate group is 42. The molecular weight of the constituent unit derived from 2-hydroxyethyl acrylate, which is a monomer having a crosslinkable functional group, is 116.

[0214] Calculation formula (1) Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = Content of crosslinkable functional group in crosslinker (unit: mass%) / Solid content of crosslinker (unit: mass%) × Blend amount of crosslinker [amount as solid content] (unit: g) / Chemical formula amount of crosslinkable functional group (unit: g / mol) × 1000 =11.5(mass%) / 75(mass%)×0.4(g) / 42(g / mol)×1000=1.46≒1.5

[0215] Calculation formula (2) Molar number of crosslinkable functional groups in (meth)acrylic polymer A-1 [unit: mmol] = [Content of constitutional units derived from monomers having crosslinkable functional groups in (meth)acrylic polymer A-1 (unit: mass%) / 100×amount of (meth)acrylic polymer A-1 (unit: g) / molecular weight of constitutional units derived from monomers having crosslinkable functional groups (unit: g / mol)×number of crosslinkable functional groups in constitutional units derived from monomers having crosslinkable functional groups (valence)×1000] =[7.0(mass%) / 100×100(g) / 116(g / mol)×1×1000]=60.34≒60.3

[0216] Calculation formula (3) Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1 (i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1) = Value calculated using formula (1) / Value calculated using formula (2) =1.5 / 60.3=0.0248 ≒ 0.025

[0217] [Examples 2 to 19] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 3, to obtain each of the adhesive compositions of Examples 2 to 19.

[0218] [Comparative Examples 1 to 16] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 4, to obtain each of the adhesive compositions of Comparative Examples 1 to 16.

[0219] The compositions of the pressure-sensitive adhesive compositions of Examples 1 to 19 and Comparative Examples 1 to 16, and the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A] are shown in Tables 3 and 4.

[0220] [Table 3]

[0221] [Table 4]

[0222] Details of the crosslinking agents listed in Table 3 and / or Table 4 are as follows. "XDI" [Product name: Takenate (registered trademark) D-110N, xylylene diisocyanate compound (adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP)), isocyanate group content: 11.5% by mass, solid content: 75% by mass, manufactured by Mitsui Chemicals, Inc.] "TDI" [Product name: Coronate (registered trademark) L-45E, tolylene diisocyanate compound (adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP)), isocyanate group content: 7.9% by mass, solid content: 45% by mass, manufactured by Tosoh Corporation] "HMDI" [Product name: Sumidur (registered trademark) N75, hexamethylene diisocyanate compound (biuret of hexamethylene diisocyanate (HMDI)), isocyanate group content: 16.5% by mass, solid content: 75% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.] "Aluminum chelate" [Aluminum chelate A (trade name, chemical name: aluminum tris(acetylacetonate), molecular weight: 324) manufactured by Kawaken Fine Chemical Co., Ltd. was diluted with acetylacetone and ethyl acetate, solids concentration: 3.24% by mass] The above "Takenate," "Coronate," and "Sumidur" are all registered trademarks.

[0223] Details of the silicone compounds described in Table 3 and / or Table 4 are as follows. <Silicone compound with epoxy groups on the side chain> "KF-101" [Product name, kinetic viscosity at 25°C: 1500mm 2 / s, Shin-Etsu Chemical Co., Ltd., specific silicone compound (C)] "X-22-343" [Product name, kinematic viscosity at 25°C: 25mm 2 / s, Shin-Etsu Chemical Co., Ltd., specific silicone compound (C)] <Silicone compound having polyether groups in the side chain> "FZ-2110" [Product name: DOWSIL (registered trademark) FZ-2110, kinematic viscosity at 25°C: 130 mm 2 / s, Dow Toray Industries, Inc., specific silicone compound (C) <Silicone compound having epoxy and polyether groups in the side chain> "BY16-760" [Product name: DOWSIL (registered trademark) BY 16-760, kinematic viscosity at 25°C: 1500mm 2 / s, Dow Toray Industries, Inc., specific silicone compound (C) "BY16-876" [Product name: DOWSIL (registered trademark) BY 16-876, kinematic viscosity at 25°C: 2400mm 2 / s, manufactured by Dow Toray Co., Ltd. <Silicone compound with amino group on the side chain> "SF8417" [Product name: DOWSIL (registered trademark) SF 8417, kinematic viscosity at 25°C: 1200mm 2 / s, manufactured by Dow Toray Co., Ltd.

[0224] In Tables 3 and 4, the values ​​shown in the "Amount blended" column for (meth)acrylic polymer A, (meth)acrylic copolymer B, and crosslinking agent are all values ​​calculated as solid contents. In Tables 3 and 4, the numerical values ​​shown in the "Amount of silicone compound" column are values ​​calculated as the active ingredient. In Table 4, "-" means that the ingredient in that column was not included.

[0225] [Preparation of adhesive sheets for evaluation] The adhesive composition prepared above was applied to the easy-adhesion treated surface of a polyethylene terephthalate (PET) film [trade name: Teijin (registered trademark) Tetoron (registered trademark) film, model number: G2P2, thickness: 50 μm, manufactured by Teijin Film Solutions Co., Ltd.] so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C and a drying time of 1 minute, forming an adhesive film on the PET film. Next, the surface on which the adhesive film was exposed was laminated on the release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been easily peeled with a separately prepared silicone-based release treatment agent, and then the film was left to stand for 4 days in an environment of an atmospheric temperature of 23 ° C and 50% RH to be aged, and an evaluation adhesive sheet was prepared. The prepared pressure-sensitive adhesive sheet for evaluation had a laminated structure of release film / pressure-sensitive adhesive layer / PET film.

[0226] [Measurement and Evaluation] 1. Gel fraction The gel fraction after crosslinking (i.e., the gel fraction of the pressure-sensitive adhesive layer) was measured using the pressure-sensitive adhesive composition prepared above. Specifically, it was measured by the following method. The adhesive composition was applied to the release-treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a silicone-based release treatment agent, so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on the release-treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a separately prepared silicone-based release treatment agent, and then left to stand for 4 days in an environment of an atmospheric temperature of 23 ° C. and 50% RH to be aged, to produce a non-substrate type adhesive sheet. The pressure-sensitive adhesive sheet thus produced has a laminated structure of release film / pressure-sensitive adhesive layer / release film.

[0227] The gel fraction of the pressure-sensitive adhesive layer peeled off from the obtained pressure-sensitive adhesive sheet was measured according to the following (1) to (4). The results are shown in Tables 5 and 6. (1) About 0.15 g of the adhesive layer is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer on the inside to prevent the gel from leaking out, to prepare a sample. After that, the mass is accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) Take out the sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, measure the mass accurately using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).

[0228] 2. Initial adhesion The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of a polyimide (PI) sheet [trade name: Kapton (registered trademark) 100H, manufactured by Toray DuPont Co., Ltd.] (hereinafter simply referred to as "PI") laminated to a stainless steel (so-called SUS) plate, and then pressed by moving a 2 kg roller back and forth once to prepare a test piece X-1. The prepared test piece X-1 was left to stand for 30 minutes in an environment of an atmospheric temperature of 23°C and 50% RH. After leaving the test piece X-1 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the pressure-sensitive adhesive layer exhibited easy peelability at the initial stage of bonding.

[0229] -Evaluation criteria- A: The adhesive strength is 0.01N / 25mm or more and less than 0.40N / 25mm. B: The adhesive strength is 0.40N / 25mm or more and less than 1.00N / 25mm. C: The adhesive strength is 1.00N / 25mm or more.

[0230] 3. Adhesive strength over time The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of the PI laminated to the SUS plate, and then a 2 kg roller was moved back and forth once to press the surface, and test piece X-2 was prepared. The prepared test piece X-2 was left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH. After leaving the test piece X-2 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column type material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the adhesive layer was one whose easy peelability at the initial stage of bonding was unlikely to deteriorate over time.

[0231] -Evaluation criteria- A: The adhesive strength is 0.01N / 25mm or more and less than 0.75N / 25mm. B: The adhesive strength is 0.75N / 25mm or more and less than 1.00N / 25mm. C: The adhesive strength is 1.00N / 25mm or more.

[0232] 4. Adhesive strength after heating The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of the PI laminated to the SUS plate, and then a 2 kg roller was moved back and forth once to press the two pieces together to prepare a test piece X-3. The prepared test piece X-3 was left in a dryer set at a temperature of 50°C for 20 minutes, then removed from the dryer and left in an environment with an atmospheric temperature of 23°C and 50% RH for 30 minutes. After leaving the test piece X-3 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the adhesive layer exhibited high adhesive strength after heating.

[0233] -Evaluation criteria- A: The adhesive strength is 9.00N / 25mm or more. B: The adhesive strength is 7.00N / 25mm or more and less than 9.00N / 25mm. C: The adhesive strength is less than 7.00N / 25mm.

[0234] [Table 5]

[0235] [Table 6]

[0236] As shown in Table 5, it was confirmed that the adhesive layers formed using the adhesive compositions of Examples 1 to 19 exhibited easy peelability when initially attached to the adherend, that this easy peelability was not easily lost over time, and that they exhibited high adhesive strength after heating.

[0237] On the other hand, as shown in Table 6, it was confirmed that the adhesive layers formed using the adhesive compositions of Comparative Examples 1 to 16 showed results inferior to the adhesive layers formed using the adhesive compositions of the Examples in at least one evaluation of the easy peelability at the beginning of lamination, the easy peelability over time after lamination, and the adhesive strength after heating.

Claims

1. A (meth)acrylic polymer (A) containing a structural unit derived from a monomer having a crosslinkable functional group and having a glass transition temperature of less than 0°C; a (meth)acrylic copolymer (B) containing 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, based on all structural units, having a glass transition temperature of 20° C. to 50° C., and having a weight average molecular weight of 10,000 to 400,000; It has at least one of an epoxy group and a polyether group in the side chain, and has a kinetic viscosity of 2000 mm at 25°C. 2 / s or less; and A cross-linking agent; Including, the crosslinkable functional group is at least one of a hydroxyl group and a carboxy group, the number average molecular weight of the monomer having an organosiloxane skeleton in the (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000; the content of the (meth)acrylic copolymer (B) is 0.1 parts by mass to 21 parts by mass based on 100 parts by mass of the (meth)acrylic polymer (A); The pressure-sensitive adhesive composition, wherein the content of the silicone compound (C) is 0.1 to 10 parts by mass based on 100 parts by mass of the (meth)acrylic polymer (A).

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the monomer having an organosiloxane skeleton is a compound represented by the following formula (I): 【Chemistry 1】 In formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group. m and n each independently represent 0 or an integer of 1 or more, provided that m and n are not 0 at the same time.

3. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1 or 2.

4. An optical member comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Double-sided self-adhesive sheet for processing plate-like member and method of processing plate-like member

    JP2009132867A

  • Adhesive composition, adhesive layer and adhesive sheet

    JP2014224227A

  • Adhesive sheet and display body

    JP2016216624A

  • Adhesive composition, adhesive layer and adhesive sheet

    JP2017203164A

  • Adhesive composition for protective film, and protective film

    JP2019035066A